Design of Smart Garden Based On The Internet of Things (IoT) - Atmiasri; Andika Tri Wiyono (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2021)
Currently, the control of cultivated plants is still manual, where farmers watering and checking soil moisture on the planting object. However, we cannot avoid technological progress in this life because technological progress will run following scientific advances. Therefore, every innovation is created to provide positive benefits for life. The ideal chili cultivation planning requires information about climatic conditions that play a significant role in chili cultivation is rainfall. Plant growth will be incredible if there is sufficient water supply; humidity for chili plants ranges from 60-80%. Therefore, chili cultivation planning must pay attention to rainfall because related to water availability. Smart Garden prototype design is a solution for taking appropriate actions during extreme weather and reducing human error. A prototype Smart Garden-based Internet of Things (IoT) using the Blynk app as User Interface (GUI) in the monitoring system and using the Soil Moisture sensor as input for soil moisture conditions, where the results of the process are sent via Wemos D1 mini-module to the Blynk server to display the state of soil moisture and automatic watering.